2003
DOI: 10.1088/0957-4484/15/1/042
|View full text |Cite
|
Sign up to set email alerts
|

Wall structure and surface chemistry of hydrothermal carbon nanofibres

Abstract: A transmission electron microscopy examination of hydrothermally produced carbon nanofibres/nanotubes with outer diameter 50-200 nm suggests that the tube walls are inclined with respect to the tube axis. The apex angles are in the range 8 •-16 •. The structure of these tubes and their growth mechanism can be described by a conical-scroll model. The conical-scroll structure enables functionalization of both inner and outer tube surfaces. The outer wall of these nanofibres is shown to be covered by a hair-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 21 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…A higher resolution TEM image [see Fig. 4(b)] reveals the finer detail of this conical scroll structure, which is similar to the one described in [15]. Finally, the same image shows that tube surface also possesses a "herringbone" wall structure and chemically stable arched edges [16] that were induced by the 3000 C heat treatment employed to graphitize the carbon and remove the catalyst.…”
Section: Methodssupporting
confidence: 61%
“…A higher resolution TEM image [see Fig. 4(b)] reveals the finer detail of this conical scroll structure, which is similar to the one described in [15]. Finally, the same image shows that tube surface also possesses a "herringbone" wall structure and chemically stable arched edges [16] that were induced by the 3000 C heat treatment employed to graphitize the carbon and remove the catalyst.…”
Section: Methodssupporting
confidence: 61%
“…73 Further investigation by EELS suggested that the "hairs" were functional groups containing oxygen and carbon, thus corroborating the hydrophilic behavior of the as-synthesized CNFs.…”
Section: Electron Energy Loss Spectroscopymentioning
confidence: 67%
“…108 The chemical stability of CNFs allow their surface chemistry to be controlled with variable wettability; both hydrophobic 40,109,110 and hydrophilic 40,48,73,111 surfaces have been demonstrated. Chemical, biochemical, and electrochemical functionalizations of VACNF material are often preceded by an oxidation step in which amorphous material is removed and oxygen-containing moieties are generated on the surface; most commonly noted are carboxyl surface terminus species.…”
Section: Chemical Functionalizationmentioning
confidence: 99%
“…[4] For this reason, the search for new synthetic strategies for the generation of carbon materials with controllable microand nanostructures has been an appealing topic in materials chemistry. This is because of the many important applications of these materials, for example, as adsorbents, filter materials, [5] catalyst supports, [6] electrode materials, [7] energy-storage materials, [8] or stationary phases in liquid chromatography.…”
Section: Introductionmentioning
confidence: 99%